1999
DOI: 10.2307/2656953
|View full text |Cite
|
Sign up to set email alerts
|

Covariance and decoupling of floral and vegetative traits in nine Neotropical plants: a re‐evaluation of Berg's correlation‐pleiades concept

Abstract: Nearly forty years ago R. L. Berg proposed that plants with specialized pollination ecology evolve genetic and developmental systems that decouple floral morphology from phenotypic variation in vegetative traits. These species evolve separate floral and vegetative trait clusters, or as she termed them, "correlation pleiades." The predictions of this hypothesis have been generally supported, but only a small sample of temperate-zone herb and grass species has been tested. To further evaluate this hypothesis, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
270
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(301 citation statements)
references
References 56 publications
19
270
2
5
Order By: Relevance
“…This theory predicts that plants with specialist pollinators will have highly correlated floral organ sizes, with correlations arising by selection for floral dimensions that fit the dimensions of the pollinator, whereas plants with generalist pollinators are predicted to have less strongly correlated floral traits. However, empirical studies have shown that the relationship between pollinator specificity and the level of covariation among floral traits is not as consistent as predicted by Berg (Conner and Sterling, 1995;Armbruster et al, 1999;Brock and Weinig, 2007), suggesting that other factors may also affect floral trait correlations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory predicts that plants with specialist pollinators will have highly correlated floral organ sizes, with correlations arising by selection for floral dimensions that fit the dimensions of the pollinator, whereas plants with generalist pollinators are predicted to have less strongly correlated floral traits. However, empirical studies have shown that the relationship between pollinator specificity and the level of covariation among floral traits is not as consistent as predicted by Berg (Conner and Sterling, 1995;Armbruster et al, 1999;Brock and Weinig, 2007), suggesting that other factors may also affect floral trait correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to plants with specialist pollinators, this theory predicts that plants with generalist pollinators will experience less selection for consistent floral organ sizes and will have less independent floral and vegetative traits (Berg, 1960). Empirical studies have shown that the degree of independence of floral and vegetative traits is not well predicted by pollination syndrome; modularity of floral and vegetative organs was equally pronounced in species with unspecialized vs specialized pollination syndromes (Armbruster et al, 1999). More generally, several empirical studies have found that floral and vegetative traits are modular, such that traits within floral or vegetative modules were correlated, whereas floral and vegetative traits were generally uncorrelated (Conner and Via, 1993;Conner and Sterling, 1996;Juenger et al, 2005;Ashman and Majetic, 2006; but see Brock and Weinig, 2007), and QTL mapping in a population of recombinant inbred lines (RILs) of Arabidopsis revealed that floral and vegetative traits had largely independent genetic architectures (Juenger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for the marked heterogeneity among taxa in levels of integration, and the unexpectedly weak integration observed in the flowers of some taxa, is that flowers are not single fully integrated units. Rather, the multiple functions of the flower are each performed by distinct suites of integrated characters that share a common function but are independent of sets of structures with alternative functions, that is, floral variation/covariation may be modular [46][47][48][49]. Independence among functional modules would reduce measures of overall integration for the flower as a whole.…”
Section: Intra-floral Integration and Modularitymentioning
confidence: 99%
“…Other studies, however, have found floral colour to be constrained (Chittka 1997), possibly when pigments have dual roles in pollinator attraction and herbivory defence (Chittka et al 2001). Depending on the level of sympatry between related species, there may be selection for divergence of floral colour among close relatives to attract different pollinators, or promote pollinator constancy, without sacrificing adaptive floral morphology traits (Armbruster et al 1999;Ashman & Majetic 2006;Smith & Rausher 2008). The rapid divergence in a trait between closely related species may erase any signal for phylogenetic divergence in communities (Brooks & McLennan 1991;Losos 1996;Sargent & Ackerly 2008;Cavender-Bares et al 2009).…”
Section: Introductionmentioning
confidence: 99%